Citral protects against metabolic endotoxemia, and systemic disorders caused by high-fat diet-induced obesity via intestinal modulation - Emílio-Silva, Maycon Tavares; Rodrigues, Vinicius Peixoto; Fioravanti, Mariana Moraes; Ruiz-Malagon, Antonio Jesús; Naia Fioretto, Matheus; Raimundo, Priscila Romano; Ohara, Rie; Assunção, Renata; Bueno, Gabriela; Dario, Felipe Lima; Justulin, Luis Antonio; Rodríguez-Nogales, Alba; et al. (Frontiers in Pharmacology, 2025)
BackgroundObesity is a growing global epidemic associated with changes in the gut microenvironment and metabolic endotoxemia, which can exacerbate metabolic and inflammatory processes. Citral (CT), a monoterpene present in essential oils, has been investigated for its anti-inflammatory, antioxidant, and immunomodulatory properties. However, its role in modulating the gut axis during metabolic and inflammatory alterations in obesity remains unknown. In this study, we investigated the effects of CT on intestinal and metabolic impairment induced by lipopolysaccharide (LPS) and high-fat diet (HFD) in in vitro and in vivo models.MethodsMale C57BL/6J mice were fed a standard diet and HFD for 17 weeks, with daily oral administration of CT treatment (25, 100, or 300 mg/kg) or vehicle. Morphological and histological parameters, lipid profiles, adipose index, cytokine levels, and colonic gene expression were determined. In vitro, murine rectal carcinoma (CMT-93) cells were stimulated with LPS (10 μg/mL) to assess tight junction and inflammatory protein expression.ResultsCT treatment showed anti-obesity activity against HFD-induced body mass gain in mice, which was attributed to a significant reduction in body fat, glycemia, and cholesterol levels. Systemic inflammation during obesity also decreased after CT treatment, with a significant reduction in serum levels of endotoxin, interleukin-1β, and tumor necrosis factor-α. Additionally, CT stimulation reduced inducible nitric oxide synthase expression and maintained ZO-1 levels in LPS-stimulated CMT-93 cells.ConclusionCT has anti-obesogenic, anti-inflammatory, and anti-hyperlipidemic properties mediated by its protective effects on the intestinal epithelium in obesity. Thus, our results highlight the promising preclinical results of CT treatment as a protective agent against the detrimental effects of HFD and LPS in mice.